Effect Of Fringe Parameter On Phase Measuring Deflectometry Performance - Ang, Jia Jun (Universiti Sains Malaysia, 2021)
Phase Measuring Deflectometry (PMD) is a non-contact optical method of surface measurement, which utilizes the principle of the change of phase angle to estimate the change of surface profile. PMD is a very useful procedure as it can be applied on specular surfaces that is usually complex to be profiled by regular means of measuring technology. PMD involves the reflection of fringes over the targeted specular surface, and the change of phase in the fringe pattern due to surface profile distortion can be measured, and the overall distortion can be further calculated. To investigate the effect of fringe’s pitch of different sizes and camera lens aperture from f/5.6 to f/16 on the quality of the fringes, the first experiment is to manipulate the different lens aperture values by adjusting the camera lens used to capture the fringe and the use different size of fringe pitch that were generated. The second experiment uses the selected fringes with the highest quality, determined with the lowest Root Mean Square Error (RMSE) value, in the measurement of tilting angle of the reflective platform manipulated with a goniometer. From the result, it is found that the quality of the fringe deteriorates following a decrease of fringe brightness caused by a decrease in aperture, as well a decrease in the fringe pattern pitch size. The best quality obtainable fringe pattern is wavelength = 400 units fringe pitch with f/5.6 camera aperture, with an RMSE value of 20.64. For the second experiment, it is observed that there is at least 3 fringe pattern in the captured image in order for the phase unwrapping algorithm to work. From the result, it is also found that the pitch of fringe has a minor effect on the resolution and sensitivity of the PMD, instead, the quality of the fringe from different pitch and aperture value is having a greater impact on them.